Psychosocial distress and blood pressure among young adults: role of cortisol as mediator - Wan Omar, Wan Fatein Nabeila; Musa, Ramli; Ab Rahman, Jamalludin; Mohd Shah, Azarisman Shah; A.Talib, Norlelawati; Aung, Sithu; Abdullah, Aszrin (2018)
Introduction: Hypertension is the most prevalent risk factor of cardiovascular diseases in Malaysia. 17.3% of hypertension cases in Malaysia is attributed to adults aged 18 to 39 years. Psychosocial distress is a possible risk factor for elevated blood pressure in young adults, and cortisol could be the mediating factor. The aim of this study is to evaluate the mediating role of cortisol in hypertension and psychosocial distress in young adults.